The Classroom Management In English As A Foreign Language Classroom At State Junior High School - Luh Simariani; Dewa Ayu Eka Agustini; Adi Krisna Juniarta (Indonesian Journal Of Educational Research and Review, 2020)
This study aims to find out the way the EFL teacher manages students’ misbehavior and a big EFL classroom at junior high school. This research applied a qualitative research method. The findings of the research showed that the teacher had fulfilled the students’ needs in the classroom. Those are the needs for survival, love or belonging, freedom, power, and fun. To fulfill the survival needs the teacher improved the students’ concentration to follow the lesson. For the needs of love or belonging, the teacher ensured the students to feel that they were cared for and had comfort in the classroom. For freedom needs, the teacher makes the students feel independent and more confident. The teacher complimented the students in fulfilling the power needs of the students. Besides, the teacher made a joke in a learning activity and by doing so the fun need was met. However, the teacher did not have a specific strategy to fulfill the students’ needs.